A avaliação do desempenho docente nas perspectivas dos professores do Instituto Federal de Rondônia – Campus Vilhena - Filho, Wagner da Silva Ferreira (2021)
The need to be increasingly efficient and effective has led many organizations to adopt monitoring and performance assessment tools to ensure that the activities developed are within the intended standards. In this sense, public educational institutions also need to monitor their indicators, above all, the performance of their employees. This work aims to carry out a study on the Evaluation of Teaching Performance and to know the perspectives of the professors of the Federal Institute of Rondônia – Campus Vilhena on the subject, indicating factors to be improved in the model adopted from the perspective of the respondents. This is a case study with a quantitative-qualitative approach, which aims to examine in depth all the particularities of Campus Vilhena on this subject. The means of investigation were: the case study; bibliographical research; and the application of a questionnaire. The knowledge generated by this research reveals the respondents' perspectives on the Teacher Performance Assessment and provides the institution's heads with feedback on this process, enabling its improvement.